Process for preparing a superconductor based on oxalate - BECKER, WINFRIED (1995)
To prepare a single-phase oxide-ceramic superconductor which contains not only copper but also at least one alkaline-earth metal from the group comprising Ba, Sr, Ca and at least one metal from the group comprising Y, La, Tl, Pb or rare earths, for example YBa2Cu3O7-x, a solution is prepared which contains the metal components in the atomic ratios of the superconductor. The metals are precipitated as oxalate by combining the solution with an oxalic acid solution, and the mixture of oxalates is separated off, dried, decomposed to form the oxides and then sintered in the presence of oxygen at temperatures from 700 to 900 DEG C to form the supercondutor. The metal oxalate and the oxides formed therefrom are heated at up to 700 DEG C with an oxygen partial pressure of not more than 50 mbar, preferably in an inert gas.